New spectroscopic technique based on coaddition of surface brightness fluctuations: NGC 4449 and its stellar tidal stream - Toloba, Elisa; Martínez-Delgado, David (The astrophysical journal, 2016)
We present a new spectroscopic technique based in part on targeting the upward fluctuations of the surface brightness for studying the internal stellar kinematics and metallicities of galaxies of low surface brightness effects both to galaxies and streams beyond the Local Group. The distance to these systems makes them unsuitable for targeting individual red giant branch (RGB) stars (tip of RGB at ##IMG## [http://ej.iop.org/images/0004-637X/824/1/35/apj523654ieqn1.gif] $I\gtrsim 24$ mag) and their surface brightness is too low ( ##IMG## [http://ej.iop.org/images/0004-637X/824/1/35/apj523654ieqn2.gif] $μ _r\gtrsim 25$ mag arcsec −2 ) for integrated light spectroscopic measurements. This technique overcomes these two problems by targeting individual objects that are brighter than the tip of the RGB. We apply this technique to the star-forming dwarf galaxy NGC 4449 and its stellar stream. We use Keck/DEIMOS data to measure the line-of-sight radial velocity out to ∼7 kpc in the east side of the galaxy and ∼8 kpc along the stream. We find that the two systems are likely gravitationally bound to each other and have heliocentric radial velocities of 227.3 ± 10.7 km s −1 and 225.8 ± 16.0 km s −1 , respectively. Neither the stream nor the near half of the galaxy shows a significant velocity gradient. We estimate the stellar metallicity of the stream based on the equivalent width of its calcium triplet lines and find [Fe/H] ##IMG## [http://ej.iop.org/images/0004-637X/824/1/35/apj523654ieqn3.gif] $=\quad -1.37± 0.41$ , which is consistent with the metallicity-luminosity relation for dwarf galaxies in the Local Group. Whether the stream's progenitor was moderately or severely stripped cannot be constrained with this uncertainty in metallicity. We demonstrate that this new technique can be used to measure the kinematics and (possibly) the metallicity of the numerous faint satellites and stellar streams in the halos of nearby (∼4 Mpc) galaxies.